Dual Drug Repurposing in Cervical Cancer: The Synergistic Cytotoxic Effect of Dapagliflozin-Etoricoxib and Its Predicted Modulation of PI3K/Akt/mTOR Signaling via Molecular Docking - Salih, Solafa Rabi; Majeed, Aqeela Hayder; Hussein, Kawakib Majid; Yasin, Youssef Shakuri; Jumaa, Azal Hamoody (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This study assesses the effectiveness of combining Dapagliflozin and etoricoxib in inhibiting cancer cell growth and investigates its effects on the mutant PI3K/Akt/mTOR signaling pathway to understand the underlying mechanisms. Methods: After incubation periods of 24 and 72 hours, HeLa cells and normal human fibroblasts (NHF) were utilized to assess the anticancer efficacy and safety profile of Dapagliflozin, Etoricoxib, their combination, and 5-fluorouracil (5FU). The tested concentrations ranged from 0.1 to 1000 µg/ml. To determine potential synergy and selectivity, the combination index (CI) and the selective toxicity index (SI) were estimated. Additionally, molecular docking simulations were performed to evaluate the binding affinities of Dapagliflozin and Etoricoxib to mutant proteins within the PI3K/Akt/mTOR signaling pathway. Results: The MTT assays showed that a combination of Dapagliflozin and etoricoxib has significant anticancer activity. The mixture effectively inhibits the growth of cervical cancer cells, achieving results similar to 5-fluorouracil (5FU) and outperforming Dapagliflozin or etoricoxib alone. Additionally, the cytotoxic effects of the mixture on normal human fibroblast (NHF) cells were much lower than those seen with 5FU, indicating decreased toxicity. The combined use of Dapagliflozin and etoricoxib exhibited synergistic cytotoxic effects, as indicated by the combination index (CI) score. This drug pair also showed selectivity in targeting cancer cells, as reflected by the selectivity index (SI). The molecular docking results showed that Dapagliflozin and Etoricoxib have affinities for interacting with the mutant PI3K/Akt/mTOR signaling protein. Docking scores for Dapagliflozin binding to these proteins were -8, -6.7, and -7.3 kcal/mol, while those for Etoricoxib were -8, -6.6, and -6.8 kcal/mol, respectively. Conclusion: The findings, supported by established pharmacokinetic and safety data, suggest that combining Dapagliflozin and Etoricoxib may provide a safer and more effective treatment option for cervical conditions, with a possible mechanism involving the PI3K/Akt/mTOR pathway, as predicted by molecular docking.